AGAMA DAN MORAL SISWA DALAM KAJIAN BIMBINGAN DAN KONSELING LINTAS AGAMA - Manja (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2019)
The research objective was to solve student case problems related to religious and moral issues in the study of interfaith guidance and counseling and the handling of students with religious and moral problems in the study of interfaith guidance and counseling. To answer this problem, the researcher used a case study research type with a descriptive approach. Regarding the case of students from this study that the students' religious and moral problems were handled by providing therapy, this stage was the stage of developing problem-solving strategies in counseling. The main problem in this research comes from oneself, who is less open, namely in the field of religious and moral issues, while the other factors that influence it, such as family life conditions, school conditions, mass media, friends, and the surrounding community are very influential on the formation. Personality which includes patterns of thought, character, traits, attitudes and behavior. Then the results of the therapy that have been carried out show results such as: (1) the child is able to cooperate with his friends and the relationship with the teacher is close; (2) Children have started to be active in class, as well as have started to actively ask questions about the material taught by the teacher; (3) The child begins to be confident and diligent in going to school because the biological mother pays attention to school fees; (4) His absence from school has started to decrease; (5) Indecent and rude words have begun to be abandoned; (6) Threats to classmates who are considered weak are no longer carried out; (7) Homework assignments begin and notes begin to be completed. Start speaking and behaving politely to friends and teachers.